Kinetic and Mechanism Investigation of the Reactions of Triphenylphosphine, Dialkyl Acetylenedicarboxylates and NH-Acids by Ultra Violet - Moradian, Majid; Mostafa Habibi Khorassani, Sayyed; Taher Maghsoodlou, Malek; Ebrahimi, Ali; Zakarianezhad, Mohammad; Karimi, Puya (Asian Journal of Chemistry, 2010)
The work undertaken to carry out kinetic studies of the reactions between triphenylphosphine, dialkyl acetylenedicarboxylates in the presence of NH-acid, such as 2-acetylpyrrole or 2-pyrrolecarbaldehyde. To determine the kinetic parameters of the reactions, were monitored by UV spectrophotometery. The second order fits were automatically drawn and the values of the second order rate constant (k2) were calculated using standard equations within the program. At the temperature range studied the dependence of the second order rate constant (ln k2) on reciprocal temperature was in agreement with Arrhenius equation. This provided the relevant plots to calculate the activation energy of all reactions. Furthermore, useful information were obtained from studies of the effect of solvent, structure of reactants (different alkyl groups within the dialkyl acetylenedicarboxylates and NH-acids) and also concentration of reactants on the rate of reactions. Proposed mechanism was confirmed according to the obtained results and steady state approximation and first step (k2) of reaction was recognized as a rate determining step on the basis of experimental data.